Resin materials and metal substrates
By adding components such as phosphorus-based flame-resistant agents and liquid rubber to the resin material, and combining the dispersion of inorganic fillers, the problem of taking into account the dielectric properties and flame-resistant properties of existing materials is solved, and a resin material suitable for the field of high-frequency transmission is realized.
Patent Information
- Application Number
- CN202111543702.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-14
- Filing Date
- 2021-12-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-12-16
AI Technical Summary
Existing resin materials have difficulties in improving dielectric properties and flame resistance, especially in the field of high-frequency transmission, where materials need to have both low dielectric constant and low dielectric loss, and at the same time have good flame resistance.
The resin composition is formed by adding 5 to 40 weight percent phosphorus-based flame retardant to the resin material and combining 2 to 40 weight percent liquid rubber, 5 to 60 weight percent polyphenylene ether resin and 3 to 40 weight percent crosslinking agent to the resin material to form a resin composition and uniformly dispersing the inorganic filler therein to enhance the dielectric properties and flame resistance of the material.
The resin material has good dielectric characteristics (dielectric constant less than 3.4, dielectric loss less than 0.0024) and flame resistance, which is suitable for high-frequency transmission and can be well combined with metal layers.
Smart Images

Figure CN115806735B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a resin material and a metal substrate, in particular to a halogen-free low-dielectric resin material and a metal substrate made of the same. Background Art
[0002] With the development of the fifth generation wireless system (5G), high-frequency transmission is undoubtedly the mainstream trend in order to meet the standards of 5G wireless communication. Therefore, the industry is committed to developing resin materials suitable for high-frequency transmission, and expects that they can be applied to the frequency range of 28GHz to 60GHz in the future.
[0003] In order to be applied in the field of high frequency transmission, resin materials are usually required to have the characteristics of low dielectric constant (Dk) and low dielectric dissipation factor (Df). In this specification, the dielectric constant and dielectric dissipation factor of the resin material are collectively referred to as dielectric characteristics.
[0004] The resin materials currently on the market contain a certain proportion of liquid rubber to improve the compatibility of the various components in the material and to increase the degree of cross-linking after the material is cured. However, liquid rubber cannot be added indefinitely. When the content of liquid rubber is too high, the flame retardancy of the resin material will decrease, and flame retardants need to be added separately.
[0005] Unfortunately, adding flame retardants may reduce the dielectric properties of the resin material. In other words, there is currently no resin material on the market that has both good flame retardancy and dielectric properties.
[0006] Therefore, how to improve the flame retardancy and dielectric properties of resin materials by improving the composition to overcome the above-mentioned defects has become one of the important issues that this industry wants to solve. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a resin material and a metal substrate in view of the deficiencies in the prior art.
[0008] In order to solve the above technical problems, one of the technical solutions adopted by the present invention is to provide a resin material. The resin material includes a resin composition and an inorganic filler, and the inorganic filler is dispersed in the resin composition. The resin composition includes: 2 weight percent (wt%) to 40 weight percent of a liquid rubber, 5 weight percent to 60 weight percent of a polyphenylene ether resin, 3 weight percent to 40 weight percent of a cross-linking agent, and 5 weight percent to 40 weight percent of a phosphorus-based flame retardant. The structure of the phosphorus-based flame retardant is represented by formula (I):
[0009]
[0010] Preferably, the molecular weight of the liquid rubber is 1500 g / mol to 6000 g / mol.
[0011] Preferably, the liquid rubber is synthesized from at least butadiene monomers, and with the total amount of butadiene monomers being 100 mol %, 30 mol % to 98 mol % of the butadiene monomers have vinyl-containing side chains after polymerization.
[0012] Preferably, the liquid rubber is synthesized from butadiene monomer and styrene monomer, and the content of styrene monomer in the liquid rubber is 10 mol % to 50 mol % when the total amount of the liquid rubber is 100 mol %.
[0013] Preferably, the resin material further comprises: a bismaleimide resin, wherein the total weight of the resin composition is 100 weight percent, and the content of the bismaleimide resin is 5 weight percent to 30 weight percent.
[0014] Preferably, the amount of the inorganic filler added is 20 to 150 parts by weight based on 100 parts by weight of the total weight of the resin composition.
[0015] Preferably, the inorganic filler has at least one of an acrylic group and a vinyl group through a surface treatment process.
[0016] Preferably, the inorganic filler includes at least one of silicon dioxide, strontium titanate, calcium titanate, titanium dioxide and aluminum oxide.
[0017] Preferably, the resin material further includes: a siloxane coupling agent, wherein the siloxane coupling agent has at least one of an acrylic group and a vinyl group.
[0018] Preferably, the amount of the siloxane coupling agent added is 0.1 to 5 parts by weight based on 100 parts per hundred resin (phr) of the total weight of the resin composition.
[0019] Preferably, the glass transition temperature (Tg) of the resin material is 150°C to 220°C.
[0020] In order to solve the above technical problems, another technical solution adopted by the present invention is to provide a metal substrate. The metal substrate includes a substrate layer and a metal layer disposed on the substrate layer, the substrate layer is made of a resin material, the resin material includes a resin composition and an inorganic filler, the inorganic filler is dispersed in the resin composition, and the resin composition includes: 2 weight percent to 40 weight percent of a liquid rubber, 5 weight percent to 60 weight percent of a polyphenylene ether resin, 3 weight percent to 40 weight percent of a cross-linking agent, and 5 weight percent to 40 weight percent of a phosphorus-based flame retardant. Among them, the structure of the phosphorus-based flame retardant is represented by formula (I):
[0021]
[0022] Preferably, the resin material has a dielectric loss measured at 10 GHz of less than 0.0024.
[0023] Preferably, the resin material has a dielectric constant measured at 10 GHz of less than 3.4.
[0024] Preferably, the metal substrate has a peel strength of 3.0 lb / in to 6 lb / in.
[0025] One of the beneficial effects of the present invention is that the resin material and metal substrate provided by the present invention can achieve the advantages of the resin material having both good heat resistance and dielectric properties through the technical solutions of "5 weight percent to 40 weight percent of phosphorus-based flame retardant" and "the structure of the phosphorus-based flame retardant is represented by formula (I)".
[0026] To further understand the features and technical contents of the present invention, please refer to the following detailed description of the present invention. However, the description is only provided for reference and illustration and is not intended to limit the present invention. DETAILED DESCRIPTION
[0027] The following is an explanation of the implementation methods of the "resin material and metal substrate" disclosed in the present invention through specific examples. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present invention. The following implementation methods will further explain the relevant technical content of the present invention in detail, but the disclosed content is not intended to limit the scope of protection of the present invention. In addition, the term "or" used in this article may include any one or more combinations of the associated listed items depending on the actual situation.
[0028] [Resin material]
[0029] The present invention uses a specific flame retardant to solve the problem of poor flame retardancy caused by adding too much liquid rubber in the past. After adding the flame retardant, the problem of poor dielectric properties (high dielectric constant and high dielectric loss) of the resin material will not be derived. In other words, by adding the specific flame retardant of the present invention to the resin material, the resin material can have both good flame retardancy and dielectric properties.
[0030] In addition, compared with the conventional resin composition, the resin composition of the present invention can contain a higher content of flame retardant (preferably 20 wt %) and still maintain certain dielectric properties (dielectric constant below 3.4 and dielectric loss below 0.0024).
[0031] Specifically, the resin material of the present invention includes a resin composition and an inorganic filler, wherein the inorganic filler is uniformly dispersed in the resin composition. The properties of the resin composition and the inorganic filler will be described in detail below.
[0032] [Resin composition]
[0033] The resin composition of the present invention comprises: 2 to 40 weight percent of liquid rubber, 5 to 60 weight percent of polyphenylene ether resin, 3 to 40 weight percent of a cross-linking agent, and 5 to 40 weight percent of a phosphorus-based flame retardant. The structure of the phosphorus-based flame retardant of the present invention is represented by the following formula (I):
[0034]
[0035] Through the resin composition with the above specific components and contents, the resin material of the present invention can be used to prepare a high-frequency substrate with good heat resistance and good dielectric properties, and can be applied to the field of high-frequency transmission. In addition, the high-frequency substrate can have good bonding strength with a metal layer. The characteristic tests of the resin material and the metal substrate will be described in detail later.
[0036] The resin material of the present invention contains liquid rubber, which has the characteristics of high solubility and can improve the compatibility between various components. In addition, the liquid rubber has the characteristics of reactive functional groups and can improve the cross-linking degree of the resin material after curing.
[0037] The molecular weight of the liquid rubber of the present invention is 1500 g / mol to 6000 g / mol, so that the fluidity of the resin composition can be improved and the filling property of the resin material can be further optimized. Preferably, the molecular weight of the liquid rubber is 1700 g / mol to 5500 g / mol. More preferably, the molecular weight of the liquid rubber is 2000 g / mol to 4000 g / mol.
[0038] Relative to the total weight of the resin composition being 100 weight percent, the content of the liquid rubber in the resin composition may be 1 weight percent to 40 weight percent. In some embodiments, the content of the liquid rubber in the resin composition is 2 weight percent to 35 weight percent. Preferably, the content of the liquid rubber in the resin composition is 3 weight percent to 32 weight percent.
[0039] In some embodiments, the liquid rubber includes a liquid diene rubber. Preferably, the liquid diene rubber has a high proportion of vinyl-containing side chains, and more preferably, is a liquid diene rubber having a high proportion of 1,2-vinyl side chains.
[0040] When the liquid rubber has at least one unsaturated side chain containing a vinyl group (or a vinyl group), the crosslinking density and heat resistance of the resin composition after crosslinking can be improved. Specifically, the liquid rubber is synthesized from butadiene monomers. The liquid rubber can be synthesized from butadiene monomers alone or from butadiene monomers and other monomers. In short, the liquid rubber is a butadiene homopolymer or a butadiene copolymer. Preferably, the liquid rubber is a butadiene homopolymer.
[0041] When the liquid rubber is synthesized from butadiene monomers, 30 to 98 mol percent of the butadiene monomers (after polymerization) have side chains containing vinyl groups, based on the total amount of butadiene monomers as 100 mol percent. In some embodiments, 40 mol percent, 50 mol percent, 60 mol percent, 70 mol percent, 80 mol percent, or 90 mol percent of the butadiene monomers (after polymerization) have side chains containing vinyl groups, based on the total amount of butadiene monomers as 100 mol percent.
[0042] In some embodiments, the liquid rubber is synthesized from butadiene monomer and styrene monomer. When the total amount of the liquid rubber is 100 mol%, the content of the styrene monomer in the liquid rubber is 10 mol% to 50 mol%. When the content of the styrene monomer in the liquid rubber is 10 mol% to 50 mol%, it is easy to achieve an arrangement structure similar to liquid crystal, which can improve the heat resistance and compatibility of the liquid rubber.
[0043] In some embodiments, based on the total amount of the liquid rubber as 100 mol %, the content of styrene monomer in the liquid rubber is 15 mol %, 20 mol %, 25 mol %, 30 mol %, 35 mol %, 40 mol % or 45 mol %.
[0044] The molecular weight of the polyphenylene ether resin of the present invention is 100 g / mol to 20000 g / mol; preferably, the molecular weight of the polyphenylene ether resin is 300 g / mol to 10000 g / mol; more preferably, the molecular weight of the polyphenylene ether resin is 400 g / mol to 2500 g / mol. When the molecular weight of the polyphenylene ether resin is less than 20000 g / mol, the solubility of the polyphenylene ether resin in the solvent is high, which is conducive to the preparation of the resin composition.
[0045] In some embodiments, the total weight of the resin composition is 100 weight percent, and the content of the polyphenylene ether resin is 10 weight percent to 50 weight percent. Preferably, the content of the polyphenylene ether resin is 20 weight percent to 40 weight percent. More preferably, the content of the polyphenylene ether resin is 25 weight percent to 35 weight percent.
[0046] In one example, the molecular ends of the polyphenylene ether resin may each have at least one modified group, and the modified group is selected from the group consisting of the following molecular groups: hydroxyl, amine, vinyl, styrene, methacrylate and epoxy. Preferably, the modified group is styrene or methacrylate.
[0047] The modified groups of the polyphenylene ether resin can provide unsaturated bonds to facilitate the cross-linking reaction, thereby forming a material with a high glass transition temperature and good heat resistance. In this embodiment, the molecular structure of the polyphenylene ether resin has two opposite ends each with a modified group, and the two modified groups are the same. In addition, the polyphenylene ether resin can include a single type of polyphenylene ether or multiple types of polyphenylene ethers at the same time.
[0048] In some embodiments, the polyphenylene ether resin includes a first polyphenylene ether and a second polyphenylene ether. The first polyphenylene ether and the second polyphenylene ether are independently polyphenylene ether with two terminal modification groups being hydroxyl groups, polyphenylene ether with two terminal modification groups being methacrylate groups, polyphenylene ether with two terminal modification groups being styrene groups, polyphenylene ether with two terminal modification groups being methacrylate groups, or polyphenylene ether with two terminal modification groups being epoxy groups. However, the present invention is not limited thereto.
[0049] Specifically, the weight ratio of the first polyphenylene ether to the second polyphenylene ether is 0.5 to 1.5, preferably, the weight ratio of the first polyphenylene ether to the second polyphenylene ether is 0.75 to 1.25, and more preferably, the weight ratio of the first polyphenylene ether to the second polyphenylene ether is 0.85 to 1.15.
[0050] The resin composition of the present invention may further include a bismaleimide resin. With the total weight of the resin composition as 100 weight percent, the content of the bismaleimide resin is 5 weight percent to 30 weight percent. Preferably, the content of the bismaleimide resin is 6 weight percent to 20 weight percent. More preferably, the content of the bismaleimide resin is 7 weight percent to 15 weight percent.
[0051] In some embodiments, the bismaleimide resin has at least two functional groups, so that the peel strength of the low dielectric metal substrate can be improved. However, the present invention is not limited thereto.
[0052] The weight average molecular weight of the bismaleimide resin of the present invention is 500 g / mol to 4500 g / mol. Preferably, the weight average molecular weight of the bismaleimide resin is 500 g / mol to 3500 g / mol. More preferably, the weight average molecular weight of the bismaleimide resin is 500 g / mol to 3000 g / mol.
[0053] The crosslinking agent of the present invention can improve the degree of crosslinking between the polyphenylene ether resin and the liquid rubber. In the present embodiment, the crosslinking agent may include an allyl group. For example, the crosslinking agent may be triallylcyanurate (TAC), triallyl isocyanurate (TAIC), diallyl phthalate, divinylbenzene, triallyltrimellitate or any combination thereof. Preferably, the crosslinking agent is triallyl isocyanurate. However, the present invention is not limited thereto.
[0054] In some embodiments, the content of the cross-linking agent is 3 to 37 weight percent, based on the total weight of the resin composition being 100 weight percent. Preferably, the content of the cross-linking agent is 5 to 35 weight percent. More preferably, the content of the cross-linking agent is 7 to 30 weight percent.
[0055] The phosphorus-based flame retardant of the present invention can be prepared by the following method, however, the phosphorus-based flame retardant is not limited to being prepared by this method.
[0056] In an exemplary embodiment, 432 g (2 mol) of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, DOPO), 251 g (1 mol) of biphenyl dichlorobenzyl and 2400 g of are added to a stirring tank, and heated and stirred for 16 hours at a temperature of 170°C to allow the reaction to produce a solution. After the solution is cooled to room temperature, hexane is added to wash the product, and a white crystalline product can be obtained after filtering. Then, the white crystalline product is baked at a temperature of 120°C to obtain the phosphorus flame retardant of the present invention.
[0057] By adding the phosphorus flame retardant of formula (I), the resin material of the present invention can have good dielectric properties (dielectric constant less than 3.4 and dielectric loss less than 0.0024). Compared with the conventional resin materials, the resin material can have a higher amount of flame retardant added (greater than 20 weight percent).
[0058] In some embodiments, the content of the phosphorus-based flame retardant of the present invention is 10 weight percent to 38 weight percent, based on the total weight of the resin composition as 100 weight percent. Preferably, the content of the phosphorus-based flame retardant of the present invention is 15 weight percent to 35 weight percent. More preferably, the content of the phosphorus-based flame retardant of the present invention is 25 weight percent to 32 weight percent.
[0059] [Inorganic filler]
[0060] The addition of inorganic fillers can help reduce the viscosity of the resin material and can also help reduce the dielectric constant of the resin material. For some types of inorganic fillers, the inorganic fillers may also improve the thermal conductivity of the resin material. The above description is only a general description and is not limited to this.
[0061] In the present invention, the inorganic filler may include: silicon dioxide, strontium titanate, calcium titanate, titanium dioxide, aluminum oxide or a combination thereof. However, the present invention is not limited thereto. In a preferred embodiment, the inorganic filler includes silicon dioxide, aluminum oxide and titanium dioxide at the same time, and titanium dioxide may be replaced by strontium titanate, calcium titanate or a combination thereof. The silicon dioxide may be molten or crystalline silicon dioxide. Preferably, the silicon dioxide is molten silicon dioxide.
[0062] In a preferred embodiment, the inorganic filler is surface treated so that the surface of the inorganic filler has at least one of an acrylic base and a vinyl base. In this way, the inorganic filler can react with the liquid rubber and has good compatibility with the rubber resin composition without negatively affecting the heat resistance of the metal substrate. Therefore, the resin material of the present invention is more suitable as a high-frequency substrate material.
[0063] It is worth noting that the inorganic filler can be a single component or a mixture of multiple components. In addition, the inorganic filler can be completely surface treated to have at least one of an acrylic base and a vinyl group, or only a portion of the inorganic filler can be surface treated to have at least one of an acrylic base and a vinyl group. For example, when the inorganic filler includes silicon dioxide and aluminum oxide, one embodiment is that the silicon dioxide is surface-modified to have at least one of an acrylic base and a vinyl group, while the aluminum oxide is not surface-modified. However, the above example is only one feasible embodiment and is not intended to limit the present invention.
[0064] The inorganic filler is spherical in shape, has an average particle size (D50) of 0.3 microns to 3 microns, and has a maximum particle size (D99) of less than 10 microns, so that the inorganic filler can be evenly dispersed in the rubber resin composition.
[0065] The amount of inorganic filler added can be adjusted according to the product specification requirements. In some embodiments, the amount of inorganic filler added is 20 to 150 parts by weight relative to 100 parts by weight of the resin composition. Preferably, the amount of inorganic filler added is 30 to 120 parts by weight. More preferably, the amount of inorganic filler added is 40 to 100 parts by weight. However, the above example is only one feasible embodiment and is not intended to limit the present invention.
[0066] [Siloxane coupling agent]
[0067] The resin material may further include a siloxane coupling agent. The addition of the siloxane coupling agent can enhance the reactivity and compatibility between the fiber cloth, the resin composition and the inorganic filler, thereby enhancing the peeling strength and heat resistance of the metal substrate.
[0068] In a preferred embodiment, the siloxane coupling agent has at least one of an acrylic group and a vinyl group. The molecular weight of the siloxane coupling agent is 100 g / mol to 500 g / mol. Preferably, the molecular weight of the siloxane coupling agent is 110 g / mol to 250 g / mol. More preferably, the molecular weight of the siloxane coupling agent is 120 g / mol to 200 g / mol.
[0069] The content of the siloxane coupling agent is 0.1 to 5 parts by weight relative to 100 parts by weight of the total weight of the resin composition. Preferably, the content of the siloxane coupling agent is 0.5 to 3 parts by weight.
[0070] [catalyst]
[0071] The resin material may further include a catalyst, which can help the resin material solidify to form a high-frequency substrate. The content of the catalyst is 0.1 to 1 parts by weight relative to 100 parts by weight of the total weight of the resin composition.
[0072] For example, the catalyst may be an imidazole compound, such as triphenylimidazole, 2-ethyl-4-methylimidazole (2E4MZ), 1-Benzyl-2-phenylimidazole (1B2PZ), 1-cyanoethyl-2-phenylimidazole (2PZ-CN), or 2,3-dihydro-1H-pyrrole[1,2-a]benzimidazole (TBZ). However, the present invention is not limited to the above examples.
[0073] [Characteristic test]
[0074] In order to verify that the resin material of the present invention can be used as a high-frequency substrate material, the present invention mixes 2 to 40 weight percent of liquid rubber, 5 to 60 weight percent of polyphenylene ether resin, 5 to 30 weight percent of bismaleimide resin, 3 to 40 weight percent of cross-linking agent, and 5 to 40 weight percent of phosphorus flame retardant to form a resin composition, and then mixes inorganic filler into the resin composition to form the resin materials of Examples 1 to 4 and Comparative Examples 1 to 10. The component ratios of the resin materials in Examples 1 to 4 and Comparative Examples 1 to 10 are shown in Table 1. The glass transition temperature, dielectric constant, and dielectric loss of the resin materials in Examples 1 to 4 and Comparative Examples 1 to 10 are shown in Table 2.
[0075] Next, a glass fiber cloth is immersed in the resin materials of Examples 1 to 4 and Comparative Examples 1 to 10, respectively, and a prepreg is obtained after the steps of impregnation, drying and molding. The prepreg is processed and a metal layer is provided on the prepreg to obtain the metal substrates of Examples 1 to 4 and Comparative Examples 1 to 10. The peel strength and heat resistance of the metal substrates of Examples 1 to 4 and Comparative Examples 1 to 10 are shown in Table 2.
[0076] In Table 1, the molecular weight of polybutadiene A is 1200 g / mol, and polybutadiene A contains 85 mole percent of 1,2-vinyl side chains. The molecular weight of polybutadiene B is 2100 g / mol, and polybutadiene B contains more than 90 mole percent of 1,2-vinyl side chains. The molecular weight of butadiene / styrene / divinylbenzene branched terpolymer is 5300 g / mol. The molecular weight of butadiene / styrene copolymer is 8600 g / mol, and the butadiene / styrene copolymer contains 17 to 27 mole percent of styrene monomer, and the butadiene / styrene copolymer contains 40 mole percent of 1,2-vinyl side chains. The molecular weight of polybutadiene C is 3000 g / mol, and polybutadiene C contains 70 to 80 mole percent of 1,2-vinyl side chains.
[0077] In Table 2, the way to evaluate the characteristics of the resin material / metal substrate is as follows:
[0078] (1) Glass transition temperature: The glass transition temperature of the resin material was tested using a dynamic mechanical analyzer (DMA).
[0079] (2) Dielectric constant (10 GHz): A dielectric analyzer (HP Agilent E4991A) was used to test the dielectric constant of the resin material at a frequency of 10 GHz.
[0080] (3) Dielectric loss (10 GHz): A dielectric analyzer (HP Agilent E4991A) was used to test the dielectric loss of the resin material at a frequency of 10 GHz.
[0081] (4) Peel strength test: According to the IPC-TM-650-2.4.8 test method, the peel strength of the metal substrate is tested.
[0082] (5) Heat resistance: Heat the metal substrate in a pressure cooker at 120°C and 2 atm for 120 minutes, then immerse it in a 288°C soldering furnace, and record the time required for the board to burst. If the board burst time exceeds 10 minutes, it is indicated as "OK", and if the board burst time is shorter than 10 minutes, it is indicated as "NG".
[0083]
[0084]
[0085] According to the contents of Table 1 and Table 2, the use of the phosphorus flame retardant of the present invention can make the resin material have both good flame retardancy and dielectric properties. Specifically, the dielectric constant of the resin material of the present invention can be lower than 3.4, and the dielectric loss is lower than 0.0024, which are better than the dielectric properties of Comparative Examples 1 to 10 (using the phosphorus flame retardant on the market).
[0086] According to the contents of Examples 1 to 4, the glass transition temperature of the resin material of the present invention is 150° C. to 220° C., and the peel strength of the metal substrate is 3.2 lb / in to 5.5 lb / in.
[0087] According to the contents of Examples 1 to 4, adding liquid rubber in different proportions will affect the dielectric properties of the resin material. When the content of the liquid rubber accounts for 3 to 30 weight percent of the resin composition, the resin material can have good dielectric properties. In particular, when the content of the liquid rubber accounts for 15 to 25 weight percent of the resin composition, the dielectric constant of the resin material can be lower than 3.1, and the dielectric loss is lower than 0.0024.
[0088] According to the results of Example 5, when the liquid rubber is synthesized from butadiene monomer and styrene monomer, and the content of styrene monomer in the liquid rubber is 10 mol % to 50 mol %, the metal substrate can have a better glass transition temperature.
[0089] [Beneficial Effects of Embodiments]
[0090] One of the beneficial effects of the present invention is that the resin material and metal substrate provided by the present invention can achieve the advantages of the resin material having both good heat resistance and dielectric properties through the technical solutions of "5 weight percent to 40 weight percent of phosphorus-based flame retardant" and "the structure of the phosphorus-based flame retardant is represented by formula (I)".
[0091] Furthermore, the resin material and metal substrate provided by the present invention can achieve the effect of improving the fluidity of the resin composition and further optimizing the filling property of the resin material through the technical solution of "the molecular weight of the liquid rubber is 1500g / mol to 6000g / mol".
[0092] Furthermore, the resin material and metal substrate provided by the present invention can improve the peel strength and heat resistance of the metal substrate through the technical solution of "the total weight of butadiene monomer is 100 mol%, and 30 mol% to 98 mol% of the butadiene monomer has a vinyl-containing side chain after polymerization".
[0093] Furthermore, the resin material and metal substrate provided by the present invention can improve the heat resistance of the metal substrate through the technical solution of "the liquid rubber is synthesized from butadiene monomer and styrene monomer, the total amount of the liquid rubber is 100 mol percent, and the content of styrene monomer in the liquid rubber is 10 mol percent to 50 mol percent."
[0094] Furthermore, the resin material and metal substrate provided by the present invention can improve the peeling strength and heat resistance of the metal substrate through the technical solution of "the siloxane coupling agent has at least one of an acrylic group and a vinyl group".
[0095] The contents disclosed above are only preferred feasible embodiments of the present invention, and are not intended to limit the protection scope of the claims of the present invention. Therefore, all equivalent technical changes made using the contents of the present invention specification are included in the protection scope of the claims of the present invention.
Claims
1. A resin material, characterized in that: The resin material includes a resin composition and an inorganic filler, wherein the inorganic filler is dispersed in the resin composition, and the resin composition includes: -Liquid rubber; 25 to 35 weight percent of a polyphenylene ether resin having methacrylate groups at one or both ends; 7 to 30 weight percent of a cross-linking agent; and A phosphorus flame retardant, wherein the structure of the phosphorus flame retardant is represented by formula (I): Wherein, the liquid rubber is polybutadiene or butadiene / styrene copolymer; the liquid rubber is synthesized from at least butadiene monomer, and with the total amount of the butadiene monomer being 100 mol %, 30 mol % to 98 mol % of the butadiene monomer has a vinyl-containing side chain after polymerization; The content of the phosphorus flame retardant accounts for 25 weight percent to 32 weight percent of the resin composition and the content of the liquid rubber accounts for 15 weight percent to 25 weight percent of the resin composition, so that the dielectric constant of the resin material measured at 10 GHz is less than 3.1; Wherein, the average particle size of the inorganic filler is 0.3 microns to 3 microns.
2. The resin material according to claim 1, characterized in that The molecular weight of the liquid rubber is 1500 g / mol to 6000 g / mol.
3. The resin material according to claim 1, characterized in that The butadiene / styrene copolymer is synthesized from butadiene monomer and styrene monomer. Taking the total amount of the liquid rubber as 100 mol percent, the content of the styrene monomer in the liquid rubber is 10 mol percent to 50 mol percent.
4. The resin material according to claim 1, characterized in that The resin material further includes: a bismaleimide resin, and the content of the bismaleimide resin is 5 weight percent to 30 weight percent based on the total weight of the resin material being 100 weight percent.
5. The resin material according to claim 1, characterized in that Based on 100 parts by weight of the total weight of the resin composition, the content of the inorganic filler is 20 parts by weight to 150 parts by weight.
6. The resin material according to claim 1, characterized in that The inorganic filler has at least one of an acrylic group and a vinyl group through a surface treatment process.
7. The resin material according to claim 1, characterized in that The inorganic filler includes at least one of silicon dioxide, strontium titanate, calcium titanate, titanium dioxide and aluminum oxide.
8. The resin material according to claim 1, characterized in that The resin material further includes: a siloxane coupling agent, wherein the siloxane coupling agent has at least one of an acrylic group and a vinyl group.
9. The resin material according to claim 8, characterized in that Based on 100 parts by weight of the total weight of the resin composition, the content of the siloxane coupling agent is 0.1 parts by weight to 5 parts by weight.
10. The resin material according to claim 1, characterized in that The resin material has a glass transition temperature of 150°C to 220°C.
11. A metal substrate, characterized in that: The metal substrate comprises: a base material layer and a metal layer disposed on the base material layer, wherein the base material layer is made of a resin material, wherein the resin material comprises a resin composition and an inorganic filler, wherein the inorganic filler is dispersed in the resin composition, and wherein the resin composition comprises: -Liquid rubber; 25 to 35 weight percent of a polyphenylene ether resin having methacrylate groups at one or both ends; 7 to 30 weight percent of a cross-linking agent; and A phosphorus flame retardant; The structure of the phosphorus flame retardant is represented by formula (I): Wherein, the liquid rubber is polybutadiene or butadiene / styrene copolymer; the liquid rubber is synthesized from at least butadiene monomer, and with the total amount of the butadiene monomer being 100 mol %, 30 mol % to 98 mol % of the butadiene monomer has a vinyl-containing side chain after polymerization; The content of the phosphorus flame retardant accounts for 25 weight percent to 32 weight percent of the resin composition and the content of the liquid rubber accounts for 15 weight percent to 25 weight percent of the resin composition, so that the dielectric constant of the resin material measured at 10 GHz is less than 3.1; Wherein, the average particle size of the inorganic filler is 0.3 microns to 3 microns.
12. The metal substrate according to claim 11, characterized in that: The resin material has a dielectric loss measured at 10 GHz that is less than 0.0024.
13. The metal substrate according to claim 11, characterized in that: The metal substrate has a peel strength of 3.0 lb / in to 6 lb / in.
Citation Information
Patent Citations
Resin composition
CN105936745A
Modified polyphenyl ether resin, preparation method thereof and resin composition
CN106928446A